Zur Frage einer Rissvereisung des Südschwarzwaldes - Reichelt, Günther (ERDKUNDE, 1960)
A glaciation of the Schwarzwald during the Riss period, though long presumed, had not so far been proved. Investigations in the southernmost part of the Schwarzwald, the Hotzenwald, in 1951-1958 have brought forth new material justifying the conclusion that this part of the Schwarzwald was indeed glacier covered in the Riss period. The existence of a Riss glaciation is supported as follows: Gravel analyses of the relevant material regarding the degree of roundness resulted clearly in a moraine spectrum; on the basis of the individual spectra both solifluidal and fluviatile transport could be excluded. The degree of weathering of these gravel bodies (they consist on an average of 48 % fresh gravel) is considerably higher than in the case of typical Würm moraines (where the average is 78 % fresh gravel). Since in the Riss period the Alpine Aare-Rhine glacier pushed up on the southern edge of the Hotzenwald to maximally about 600 m. above sea level, the degree of weathering of the above mentioned deposits can be compared directly with that of the Alpine Riss glaciers. The degree of agreement is high. In some instances, according to composition, deposition, degree of weathering and rounding, it appears that Alpine Riss moraines (from the south-east) and Schwarzwald Riss moraines (from the north) are interlaced in the area Hanner-Rotzel; thus a meeting or mutual superposition of Alpine and Schwarzwald ice bodies in the Riss period can be inferred. Outlining the areas covered with ice in the Riss and Würm periods shows that the glaciation of the Hotzenwald was considerably more extensive than has been assumed so far. An the whole the investigation led to similar conclusions as those independently reached by Pfannenstiel (in the meantime published, see postscript) for the eastward adjoining area; they greatly supplement the picture of the glaciated part of the western Hotzenwald.